EXTENDING THE SERVICE LIFE OF CONVEYOR BELTS USED IN FOOD PRODUCTION ENTERPRISES (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article discusses the improvement of technological equipment used in food enterprises, the widespread use of conveyor transport, the study of fatigue wear properties of rubber-fabric belts, and the development of practical recommendations to extend their service life.